2012
DOI: 10.1007/s10773-012-1184-9
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matter Density from Heavy Neutrino Decays

Abstract: As we know the heavy neutrino decays is a successful model for describing dark matter and also is origin of the universe entropy. In this paper we use heavy neutrino decays to calculate time-dependent dark matter density. In that case we use observational data to fixing our solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It is also possible to study FRW cosmology of a Universe filled with CG [44]. CG equation of state (1) has been generalized to the form [24,45,46,47],…”
Section: Review Of Chaplygin Gas Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to study FRW cosmology of a Universe filled with CG [44]. CG equation of state (1) has been generalized to the form [24,45,46,47],…”
Section: Review Of Chaplygin Gas Modelmentioning
confidence: 99%
“…An important problem is determining nature of dark Universe. It is found that the dark matter may be consists of neutrinos [1] axions [2] or WIMPs (weak interactive massive particles) [3]. In that case there are several ways to specify the nature of the dark Universe.…”
Section: Introductionmentioning
confidence: 99%